2018
DOI: 10.5430/jnep.v9n5p24
|View full text |Cite
|
Sign up to set email alerts
|

Using students’ smartphones to learn a nursing skill: Students’ perspectives

Abstract: The increase in nursing students’ enrollment in post-secondary education, hospital restructuring and limited clinical placements have shifted nurses’ education to require more e-learning platforms. E-learning uses information and communication technologies to support interactions with content, learning activities and with others; and to facilitate self-reflection. Using smartphones’ video applications in a hybrid course can support learning. Most nursing students own smartphones and use them to create videos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Eleven studies reported content knowledge preparation including staff lecturing, tutoring, and instructions [ 5 , 23 , 28 , 31 , 33–35 , 42 , 46 , 50 , 51 ]. Nine studies reported providing learning resources in the form of exemplar videos or readings [ 22 , 29 , 39–44 , 52 ]. Ten studies reported student self-exploration of the topic with minimum staff input [ 10 , 12 , 32 , 36–38 , 45 , 48 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven studies reported content knowledge preparation including staff lecturing, tutoring, and instructions [ 5 , 23 , 28 , 31 , 33–35 , 42 , 46 , 50 , 51 ]. Nine studies reported providing learning resources in the form of exemplar videos or readings [ 22 , 29 , 39–44 , 52 ]. Ten studies reported student self-exploration of the topic with minimum staff input [ 10 , 12 , 32 , 36–38 , 45 , 48 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, studies showed self-reported satisfaction with video production by both students and staff [ 44 ]. Video production was regarded as enabling students to actively apply knowledge in authentic contexts [ 11 ], allowing them to self-reflect [ 52 ] and receive feedback from others [ 32 , 51 ]. Only one study indicated ease-of-use of technology, while others reported video editing being enjoyable but difficult [ 12 ], or video-making being the least positive aspect of the project [ 11 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations